The High Performance of Multi-Metal Layered Double Hydroxides (LDHs) in the Removal of Organic Dyes - Soumaya Talbi; Amal El Khanchaoui; Latifa Bouissane; Abderrafia Hafid; Mostafa Khouili; Souad Rabi; Abdellatif Essoumhi (Chemistry Proceedings)
In this work, both MgNiAl-LDH and MgNiFe-LDH hydrotalcites were utilized to remove the anionic dye Congo red (CR) from an aqueous solution. Samples characterization was carried out by X-ray diffraction (XRD), infrared spectroscopy (IR) and Thermogravimetric/Differential Scanning Calorimetry (TG/DSC). Various parameters were investigated, including the initial dye concentration, adsorbent mass, contact time, solution pH, and temperature. Using classical pseudo-first-order, pseudo-second-order, and intraparticle diffusion models, adsorption kinetics were investigated. The dynamical data fit well with the pseudo-second order kinetic model. The equilibrium adsorption data were analyzed using three linear adsorption models: Langmuir, Freundlich, and Temkin. The findings showed that the Langmuir isotherm adequately predicts experimental results with an ideal correlation coefficient. The isothermal Langmuir model revealed a maximum adsorption capacity of qmax of 5548 mg/g for the MgNiFe-LDH and of 4043 mg/g for MgNiAl-LDH. This result is very useful when selecting sorbents to improve removal technology in the aquatic environment.